2017
DOI: 10.1063/1.4985919
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulations of alkali-acetate solutions: Accuracy of the forcefields in difference concentrations

Abstract: When proteins are solvated in electrolyte solutions that contain alkali ions, the ions interact mostly with carboxylates on the protein surface. Correctly accounting for alkali-carboxylate interactions is thus important for realistic simulations of proteins. Acetates are the simplest carboxylates that are amphipathic, and experimental data for alkali acetate solutions is available and can be compared with observables obtained from simulations. We carried out molecular dynamics simulations of alkali acetate sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 83 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…See ref. [17] for details on system preparation. Briefly, the simulations were performed in a periodic cubic box with~1700 water molecules, under NpT conditions.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…See ref. [17] for details on system preparation. Briefly, the simulations were performed in a periodic cubic box with~1700 water molecules, under NpT conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The number of CIP follows the order Na + >Cs + >K + . Of note, quantum mechanical calculations (MP2) of the free energies of interaction of Cs‐acetate and K‐acetate indicated that the transfer of Cs + from a fully hydrated, [Cs ⋅ (H 2 O) 6 ] + configuration to forming a salt bridge with acetate is favoured over the formation of a K‐Acetate salt bridge . The number of SIP follows the order Cs + >K + >Na + .…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations